A quasi-experimental evaluation of an HIV prevention programme by peer education in the Anglican Church of the Western Cape, South Africa. Issue 2 (13th April 2012) - Mash, Rachel; Mash, Robert James
Abstract : Introduction: Religion is important in most African communities, but faith-based HIV prevention programmes are infrequent and very rarely evaluated. Objective: The aim of this study was to evaluate the effectiveness of a church-based peer education HIV prevention programme that focused on youth. Design: A quasi-experimental study design compared non-randomly chosen intervention and control groups. Setting: This study was conducted in the Cape Town Diocese of the Anglican Church of Southern Africa. Participants: The intervention group of 176 teenagers was selected from youth groups at 14 churches and the control group of 92 from youth groups at 17 churches. Intervention and control churches were chosen to be as similar as possible to decrease confounding. Intervention: The intervention was a 20-session peer education programme (Fikelela: Agents of Change) aimed at changing risky sexual behaviour among youth (aged 12–19 years). Three workshops were also held with parents. Primary and secondary outcome measures: The main outcome measures were changes in age of sexual debut, secondary abstinence, condom use and numbers of partners. Results: The programme was successful at increasing condom usage (condom use score 3.5 vs 2.1; p=0.02), OR 6.7 (95% CI 1.1 to 40.7), and postponing sexual debut (11.9% vs 21.4%; p=0.04) absolute difference 9.5%. There was no difference in secondary abstinence (14.6% vs 12.5%; p=0.25) or with the number of partners (mean 1.7 vs 1.4; p=0.67) and OR 2.2 (95% CI 0.7 to 7.4). Conclusion: An initial exploratory quasi-experimental evaluation of the Agents of Change peer education programme in a church-based context found that the age of sexual debut and condom usage was significantly increased. The study demonstrated the potential of faith-based peer education among youth to make a contribution to HIV prevention in Africa. Further evaluation of the effectiveness of the programme is, however, required before widespread implementation can be recommended.